Chemokine Receptor 4 Plays a Key Role in T Cell Recruitment into the Airways of Asthmatic Patients - Pandurangan Vijayanand; Kesta Durkin; Guido Hartmann; Jaymin B. Morjaria; Grégory Seumois; Karl J. Staples; David A. Hall; Christina Bessant; Michelle A. Bartholomew; Peter Howarth; Peter S. Friedmann; Ratko Djukanović (2010)
T lymphocytes of the Th2 type are central orchestrators of airway inflammation in asthma. The mechanisms that regulate their accumulation in the asthmatic airways remains poorly understood. We tested the hypothesis that CCR4, preferentially expressed on T lymphocytes of the Th2 type, plays a critical role in this process. We enumerated by flow cytometry the CCR4-expressing T cells from blood, induced sputum, and biopsy samples of patients with asthma and control subjects. We showed a positive correlation between the numbers of peripheral blood CCR4+ T cells and asthma severity, provided evidence of preferential accumulation of CCR4+ T cells in asthmatic airways, and demonstrated that CCR4+ but not CCR4- cells from patients with asthma produce Th2 cytokines. Explanted airway mucosal biopsy specimens, acquired by bronchoscopy from subjects with asthma, were challenged with allergen and the explant supernatants assayed for T cell chemotactic activity. Allergen-induced ex vivo production of the CCR4 ligand, CCL17 was raised in explants from patients with asthma when compared with healthy controls. Using chemotaxis assays, we showed that the T cell chemotactic activity generated by bronchial explants can be blocked with a selective CCR4 antagonist or by depleting CCR4+ cells from responder cells. These results provide evidence that CCR4 might play a role in allergen-driven Th2 cell accumulation in asthmatic airways. Targeting this chemokine receptor in patients with asthma might reduce Th2 cell-driven airway inflammation; therefore, CCR4 antagonists could be an effective new therapy for asthma. This study also provides wider proof of concept for using tissue explants to study immunomodulatory drugs for asthma.